2021
DOI: 10.3390/nu13072440
|View full text |Cite
|
Sign up to set email alerts
|

The Homocysteine and Metabolic Syndrome: A Mendelian Randomization Study

Abstract: Homocysteine (Hcy) is well known to be increased in the metabolic syndrome (MetS) incidence. However, it remains unclear whether the relationship is causal or not. Recently, Mendelian Randomization (MR) has been popularly used to assess the causal influence. In this study, we adopted MR to investigate the causal influence of Hcy on MetS in adults using three independent cohorts. We considered one-sample MR and two-sample MR. We analyzed one-sample MR in 5902 individuals (2090 MetS cases and 3812 controls) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Moreover, stress, poor lifestyle, age, catabolic dysregulation, and genetics can lead to abnormalities in Hcy, while abnormal Hcy levels may be considered as an etiological or risk factor in neurodegenerative diseases such as dementias, Alzheimer’s disease, Parkinson’s disease, cardiovascular diseases, and metabolic disease [ 21 23 ], but individuals in northern Italy with severe mental illness may not be at higher risk of cardiovascular disease than the general population, especially in the relatively wealthy areas and with traditional healthy dietary habits such as the Mediterranean diet [ 24 ]. A recent Mendelian Randomization study reported that in the general population, higher Hcy concentration was a risk factor for metabolic syndrome, but not for body mass index (BMI) [ 25 ], while another study reported that higher Hcy levels correlated with lower BMIs in schizophrenia patients [ 26 ]. In addition, several studies have reported that sex may also be a factor affecting Hcy in the general population [ 27 ], in bipolar disorders [ 28 ], and even in rat animal models [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stress, poor lifestyle, age, catabolic dysregulation, and genetics can lead to abnormalities in Hcy, while abnormal Hcy levels may be considered as an etiological or risk factor in neurodegenerative diseases such as dementias, Alzheimer’s disease, Parkinson’s disease, cardiovascular diseases, and metabolic disease [ 21 23 ], but individuals in northern Italy with severe mental illness may not be at higher risk of cardiovascular disease than the general population, especially in the relatively wealthy areas and with traditional healthy dietary habits such as the Mediterranean diet [ 24 ]. A recent Mendelian Randomization study reported that in the general population, higher Hcy concentration was a risk factor for metabolic syndrome, but not for body mass index (BMI) [ 25 ], while another study reported that higher Hcy levels correlated with lower BMIs in schizophrenia patients [ 26 ]. In addition, several studies have reported that sex may also be a factor affecting Hcy in the general population [ 27 ], in bipolar disorders [ 28 ], and even in rat animal models [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms involved in Hcy-associated diseases have not been entirely clarified, and whether the relationship between MetS and Hcy level is causal remains obscure. However, recently, using the Mendelian randomization approach, a significant relationship was elucidated between Hcy and the risk of MetS in the Korean population [ 110 ]. On the other hand, Hcy increases inflammatory responses and correlates with IL-6, TNFα, and hs-CRP levels [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing the risk of hypertension, HHcy increases the risk of dyslipidemia. This can be partially explained by HHcy-associated hypomethylation, which results in lipid accumulation and the downregulation of the synthesis of phosphatidylcholine that is required for very low-density lipoprotein assembly and homeostasis [ 56 ]. Low HDL-C levels are attributed to the homocysteine-induced inhibition of enzymes or molecules involved in HDL particle assembly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%